THE CHANGE OF GREETING WORDS IN BESEMAH LANGUAGE AND ITS IMPLICATION FOR LEARNING REGIONAL LANGUAGES - Resky Utami; Nurhayati Nurhayati; Sri Indrawati (English Review: Journal of English Education, 2023)
This research described the addressing terms and analyzed the addressing term shifts of Besemah community in Pagar Alam regency. This research also described the implementation of Besemah vernacular language on vernacular langauge lesson. The applied method was descriptive qualitative method and objective appraoch with four research techniques. The data source was the community of Besemah, consisting of five districts in Pagar Alam regency. The results found five hundred and fifty-two addressing terms. These words include addressing terms within family context and community context. Then, the researchers also found the shifting addressing terms. Four of the words were not found at the present days. The result implications have some implications on vernacular language lesson and could be the teaching materials for primary school levels.